2010
DOI: 10.1523/jneurosci.1216-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Metabotropic Glutamate Receptor 5 in the Amygdala Modulates Pain-Like Behavior

Abstract: The central nucleus of the amygdala (CeA) has been identified as a site of nociceptive processing important for sensitization induced by peripheral injury. However, the cellular signaling components underlying this function remain unknown. Here, we identify metabotropic glutamate receptor 5 (mGluR5) as an integral component of nociceptive processing in the CeA. Pharmacological activation of mGluRs with (R,S)-3,5-dihydroxyphenylglycine (DHPG) in the CeA of mice is sufficient to induce peripheral hypersensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
141
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(155 citation statements)
references
References 42 publications
11
141
3
Order By: Relevance
“…Accordingly, we propose that, in AIMP mice, an excessive nociceptive signal triggered by acidic saline injection into the gastrocnemius muscle activates ERK in the central amygdala, thereby enhancing PBA-CeAC synaptic transmission [see also Neugebauer et al (2003Neugebauer et al ( , 2004 and Ikeda et al (2007)]. Although the observation of increased pERK levels in the CeAC is consistent with previous studies, there is a substantial difference between the results of the present study and those of previous studies, in which mechanical hypersensitivity was shown to be functionally lateralized to the right amygdala in intraplantar formalin and arthritic models (Carrasquillo and Gereau, 2008;Ji and Neugebauer, 2009;Kolber et al, 2010). However, the results of the present study showed that functional lateralization of mechanical hypersensitivity to the right amygdala did not occur in the AIMP model.…”
Section: Pda Induces Potentiation Of Pba-ceac Synaptic Transmissionsupporting
confidence: 86%
See 1 more Smart Citation
“…Accordingly, we propose that, in AIMP mice, an excessive nociceptive signal triggered by acidic saline injection into the gastrocnemius muscle activates ERK in the central amygdala, thereby enhancing PBA-CeAC synaptic transmission [see also Neugebauer et al (2003Neugebauer et al ( , 2004 and Ikeda et al (2007)]. Although the observation of increased pERK levels in the CeAC is consistent with previous studies, there is a substantial difference between the results of the present study and those of previous studies, in which mechanical hypersensitivity was shown to be functionally lateralized to the right amygdala in intraplantar formalin and arthritic models (Carrasquillo and Gereau, 2008;Ji and Neugebauer, 2009;Kolber et al, 2010). However, the results of the present study showed that functional lateralization of mechanical hypersensitivity to the right amygdala did not occur in the AIMP model.…”
Section: Pda Induces Potentiation Of Pba-ceac Synaptic Transmissionsupporting
confidence: 86%
“…Accordingly, these observations showed that the strength of the overall synaptic inputs other than the PBA input onto CeAC neurons was also enhanced in AIMP mice, with both presynaptic and postsynaptic modulation being involved. Since previous studies have demonstrated lateralization of behavioral hypersensitivity and CeAC neuronal excitability in rats (Carrasquillo and Gereau, 2008;Ji and Neugebauer, 2009;Kolber et al, 2010), we compared aEPSC recorded from a further four left and four right CeAC neurons in slices from animals with AIMP and tested their responses to PDA application. No significant difference in the mean amplitude and the mean number of events per trial of aEPSC was found between the left and right CeAC neurons, and the values recorded from the right and left CeAC neurons were similar to the pooled data recorded from right and left CeAC neurons shown in Figure 6 (see supplemental Fig.…”
Section: Enhancement Of Synaptic Transmission In Aimp Mice Includes Pmentioning
confidence: 99%
“…However, in adult humans fearful face presentation causes event-related activation in the right amygdala and ACC (24). A number of other studies also indicated specific involvement of the right amygdala in negative emotional signaling (25)(26)(27), which suggests-along with the previously mentioned observations-the relevance of a functional asymmetry in the amygdala-ACC connection. Further studies with unilateral amygdala lesions and hemispheric difference in ACC-amygdala synchronization may provide valuable information regarding whether this brain circuit is working in social fear learning unilaterally.…”
Section: Discussionmentioning
confidence: 68%
“…mGluR5 has been implicated in various neurological and psychiatric diseases, including anxiety, depression, pain, and Alzheimer disease [9,10]. mGluR5 has also long been related to pain, since mGluR5 antagonists such as MPEP and MTEP (3-((2-Methyl-4-thiazolyl)ethynyl)pyridine) relieve pain in several animal models, and conditional mGluR5 knockout in the central nucleus of the amygdala results in the diminution of inflammation-induced hypersensitivity [22][23][24]. Interestingly, the analgesic effect of mGluR5 is reported to be mediated by its extracellular signal-regulated kinase-linked interaction with Kv4.2, the potassium channel regulated by DREAM [25].…”
Section: Discussionmentioning
confidence: 99%